2013
DOI: 10.1364/ao.52.000e40
|View full text |Cite
|
Sign up to set email alerts
|

Recording of polarization holograms in a liquid crystal cell with a photosensitive chalcogenide orientation layer [Invited]

Abstract: Polarization gratings have been recorded in a combined liquid crystal (LC) cell made of a substrate covered with a photosensitive chalcogenide orientation layer and a reference substrate covered with a rubbed polyimide film. The gratings are formed due to the spatially modulated light-induced easy orientation axis on the chalcogenide surface recorded by two beams with opposite circular polarizations. The gratings are permanent, but they can be erased by one of the recording beams and re-recorded. The diffracti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(11 citation statements)
references
References 33 publications
0
11
0
Order By: Relevance
“…Because the induced birefringence value for the Azo-Pam-II film is a bit higher, we use this material for recording of polarization diffraction gratings. The gratings are formed with the spatially modulated light-induced direction of anisotropy on the Azo-Pam-II film surface recorded by two beams with opposite circular polarizations. , The optical scheme for recording of the polarization diffraction gratings is shown in Figure S9 . We start the recording of polarization holographic gratings with the two circular oppositely polarized Gaussian beams from the Ar laser (wavelength λ = 532 nm, power P ≤ 100 mW).…”
Section: Resultsmentioning
confidence: 99%
“…Because the induced birefringence value for the Azo-Pam-II film is a bit higher, we use this material for recording of polarization diffraction gratings. The gratings are formed with the spatially modulated light-induced direction of anisotropy on the Azo-Pam-II film surface recorded by two beams with opposite circular polarizations. , The optical scheme for recording of the polarization diffraction gratings is shown in Figure S9 . We start the recording of polarization holographic gratings with the two circular oppositely polarized Gaussian beams from the Ar laser (wavelength λ = 532 nm, power P ≤ 100 mW).…”
Section: Resultsmentioning
confidence: 99%
“…Sheremet et al studied this type of photoalignment on As 2 S 3 films for a LC 5CB and on As 20 Se 80 films for LCs 5CB and E7. [3,4] The distinctive feature of the present observations is sensitivity of the photoalignment to the direction of the light irradiation; despite the equal light intensities, the alignment was achieved at the direct irradiation of the outer chalcogenide surface, and it was not observed at the irradiation through the chalcogenide layer (Figure 3(a)). The only asymmetry during the irradiation is the difference in the light intensity distribution in the case of the light beam propagating through the chalcogenide layer because of the light absorption in the chalcogenide material ( Figure 5).…”
Section: Discussionmentioning
confidence: 60%
“…The photoalignment of LC on another type of chalcogenide glass (As 20 Se 80 ) in the LC cell was also found in [3] and used for the hologram recording. [4] Gelbaor et al [5] observed a light-induced alignment of a LC after irradiation of a chalcogenide film before the cell filling. The characteristics of photoalignment at the irradiation of the chalcogenide layer before and after the cell filling were different.…”
Section: Please Scroll Down For Articlementioning
confidence: 99%
“…Therefore, many types of photoalignment materials, methods for periodic alignment, and diffraction properties of grating LC cells have been studied. [1][2][3][4][5][6][7][8][9][10][11][12] Crawford et al demonstrated the fabrication of switchable LC gratings by polarization holographic exposure on linearly photopolymerizable polymer alignment layers. 6) In the polarization holographic exposure, the intensity of the interference field is constant; however, polarization states are periodically modulated.…”
Section: Introductionmentioning
confidence: 99%